Perspectives of Microbial Inoculation for Sustainable Development and Environmental Management - Ahmad, Maqshoof; Pataczek, Lisa; Hilger, Thomas H.; Zahir, Zahir Ahmad; Hussain, Azhar; Rasche, Frank; Schafleitner, Roland; Solberg, Svein Ø. (Frontiers in Microbiology, 2018)
How to sustainably feed a growing global population is a question still without an answer. Particularly farmers, to increase production, tend to apply more fertilizers and pesticides, a trend especially predominant in developing countries. Another challenge is that industrialization and other human activities produce pollutants, which accumulate in soils or aquatic environments, contaminating them. Not only is human well-being at risk, but also environmental health. Currently, recycling, land-filling, incineration and pyrolysis are being used to reduce the concentration of toxic pollutants from contaminated sites, but too have adverse effects on the environment, producing even more resistant and highly toxic intermediate compounds. Moreover, these methods are expensive, and are difficult to execute for soil, water, and air decontamination. Alternatively, green technologies are currently being developed to degrade toxic pollutants. This review provides an overview of current research on microbial inoculation as a way to either replace or reduce the use of agrochemicals and clean environments heavily affected by pollution. Microorganism-based inoculants that enhance nutrient uptake, promote crop growth, or protect plants from pests and diseases can replace agrochemicals in food production. Several examples of how biofertilizers and biopesticides enhance crop production are discussed. Plant roots can be colonized by a variety of favourable species and genera that promote plant growth. Microbial interventions can also be used to clean contaminated sites from accumulated pesticides, heavy metals, polyaromatic hydrocarbons, and other industrial effluents. The potential of and key processes used by microorganisms for sustainable development and environmental management are discussed in this review, followed by their future prospects.